Pengembangan Model Bahan Ajar Digital Pembelajaran Matematika Kelas VI SD - Magdalena, Ina; Syafinka, Azzaya; Mariyam, Siti; Weningtyas, Zahra (MASALIQ, 2023)
Digital learning resources for teaching elementary school mathematics are the focus of this research. This qualitative study employs observation, interview, and documentation methods. This research suggests that the creation of instructional materials is essential to learning because it can assist students in better comprehending the subject matter being taught. Using a digital teaching material model, students in Class VI learned about geometric and flat shapes in this study. You can keep students' attention while they learn in a comfortable and pleasant setting by using video learning.